2009
DOI: 10.1073/pnas.0904104106
|View full text |Cite
|
Sign up to set email alerts
|

Sporulation in mycobacteria

Abstract: Mycobacteria owe their success as pathogens to their ability to persist for long periods within host cells in asymptomatic, latent forms before they opportunistically switch to the virulent state. The molecular mechanisms underlying the transition into dormancy and emergence from it are not clear. Here we show that old cultures of Mycobacterium marinum contained spores that, upon exposure to fresh medium, germinated into vegetative cells and reappeared again in stationary phase via endospore formation. They sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
91
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(100 citation statements)
references
References 36 publications
1
91
0
8
Order By: Relevance
“…This finding opens up a new hitherto to the unknown area of high G+C percent of Gram positive bacteria such as Mycobacteria. This finding is consistent with Ghosh et al [7]. They could detect dipicolinic acid in M. marinum cells of different ages using colorimetric assay method suggested by Janssen et al [10].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This finding opens up a new hitherto to the unknown area of high G+C percent of Gram positive bacteria such as Mycobacteria. This finding is consistent with Ghosh et al [7]. They could detect dipicolinic acid in M. marinum cells of different ages using colorimetric assay method suggested by Janssen et al [10].…”
Section: Discussionsupporting
confidence: 82%
“…Also, they showed that whole-cell extract of C. perfringenes NCTC 8679, a strain shown to produce spore with significant amount of DPA, indicated that DPA synthase activity in this strain was greatest 11 hours after inoculation into DSSM medium. Based on the work provided by Ghosh et al [7] and presence of some evidence in sporulation in laboratory cultures of the mycobacterial strain such as M. marinum, M. bovis bacillus Calmette-Guerin strain, finding new evidences to support this claim is important.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…W starszych kulturach Mycobacterium marinum i M. bovis BCG stwierdzono występowanie przetrwalników, a jednocześnie -podobnych w przebiegu krzywych inaktywacji cieplnej w czasie ogrzewania w temp. 65 ºC/15 min, jakie obserwuje się w przypadku Map [9]. Hipoteza, że Map w warunkach niesprzyjających (np.…”
Section: Hipotezy Ciepłooporności Mapunclassified